2001
DOI: 10.1086/318495
|View full text |Cite
|
Sign up to set email alerts
|

Etiology and Natural History of Neutropenia in Human Immunodeficiency Virus Disease: A Prospective Study

Abstract: The objective of this prospective, observational study was to define the natural history of neutropenia in human immunodeficiency virus (HIV) disease. Eighty-seven consecutive patients developing neutropenia (absolute neutrophil count [ANC], <1000 cells/mm(3)) were recruited and closely followed for the duration of the episode. Episodes lasted a median of 13 days, with a mean ANC nadir of 660 cells/mm(3). Presumed or proven infection occurred in 12 (17%) of 71 evaluable subjects, and culture-proven infection o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 26 publications
0
26
0
1
Order By: Relevance
“…21 Seven of the 12 individuals who developed infectious complications had CD4 ϩ counts less than 50 cells/mm 3 . Borg et al 22 recently reported that a low pretreatment CD4 count (Ͻ 450/mm 3 ) was an independent risk factor for febrile-neutropenia and early death in patients receiving cytotoxic chemotherapy.…”
Section: Discussionmentioning
confidence: 95%
“…21 Seven of the 12 individuals who developed infectious complications had CD4 ϩ counts less than 50 cells/mm 3 . Borg et al 22 recently reported that a low pretreatment CD4 count (Ͻ 450/mm 3 ) was an independent risk factor for febrile-neutropenia and early death in patients receiving cytotoxic chemotherapy.…”
Section: Discussionmentioning
confidence: 95%
“…Some authors argue that it could derive from the cytotoxic effects of antiviral drugs commonly used in AIDS treatment, but granulopenia also can be observed in the absence of an antiviral therapy. 45,46 Another proposed mechanism for HIV-associated granulopenia is direct infection of BM hematopoietic progenitors by HIV. Nonetheless, efforts to detect HIV infection in cultured hematopoietic progenitors either failed or were left inconclusive.…”
Section: Discussionmentioning
confidence: 99%
“…Several lines of evidence suggest that this can be attributed to a direct effect of protease inhibitors via calpaine inhibition [70,80]. Nevertheless, PMN defects are still observed in some patients who respond positively to HAART [81]. …”
Section: Effects Of Highly Active Antiretroviral Therapy On Pmn Functmentioning
confidence: 99%